Alanine Scanning Mutagenesis of the C-Terminal Cytosolic End of Gpm6a Identifies Key Residues Essential for the Formation of Filopodia - Rosas, Nicolás M.; Alvarez Juliá, Anabel; Alzuri, Sofia E.; Frasch, Alberto C.; Fuchsova, Beata (Frontiers in Molecular Neuroscience, 2018)
Neuronal membrane glycoprotein M6a (Gpm6a) is a protein with four transmembrane regions and the N- and the C-ends facing the cytosol. It functions in processes of neuronal development, outgrowth of neurites, and formation of filopodia, spines, and synapsis. Molecular mechanisms by which Gpm6a acts in these processes are not fully comprehended. Structural similarities of Gpm6a with tetraspanins led us to hypothesize that, similarly to tetraspanins, the cytoplasmic tails function as connections with cytoskeletal and/or signaling proteins. Here, we demonstrate that the C- but not the N-terminal cytosolic end of Gpm6a is required for the formation of filopodia by Gpm6a in cultured neurons from rat hippocampus and in neuroblastoma cells N2a. Further immunofluorescence microcopy and flow cytometry analysis show that deletion of neither the N- nor the C-terminal intracellular domains interferes with the recognition of Gpm6a by the function-blocking antibody directed against the extracellular part of Gpm6a. Expression levels of both truncation mutants were not affected but we observed decrease in the amount of both truncated proteins on cell surface suggesting that the incapacity of the Gpm6a lacking C-terminus to induce filopodium formation is not due to the lower amount of Gpm6a on cell surface. Following colocalization assays shows that deletion of the C- but not the N-terminus diminishes the association of Gpm6a with clathrin implying involvement of clathrin-mediated trafficking events. Next, using comprehensive alanine scanning mutagenesis of the C-terminus we identify K250, K255, and E258 as the key residues for the formation of filopodia by Gpm6a. Substitution of these charged residues with alanine also diminishes the amount of Gpm6a on cell surface and in case of K255 and E258 leads to the lower amount of total expressed protein. Subsequent bioinformatic analysis of Gpm6a amino acid sequence reveals that highly conserved and functional residues cluster preferentially within the C- and not within the N-terminus and that K250, K255, and E258 are predicted as part of sorting signals of transmembrane proteins. Altogether, our results provide evidence that filopodium outgrowth induced by Gpm6a requires functionally critical residues within the C-terminal cytoplasmic tail.